Manajemen Kebijakan Pendidikan Pemerintah Desa Di Provinsi Kepulauan Bangka Belitung - Subri Hasan (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
This research was conducted with the aim of namely; 1). Know the village government policies in developing educational institutions, children, age, early age, in Petaling village 2). Knowing the management of educational institutions, children, age, early age, in Petaling village 3). Knowing the strategies of the village government and PAUD institutions in the development of education, children, age, early age, in Petaling village. While this type of research is qualitative with descriptive analysis. The data collection tool uses observation, interview and documentation techniques.The results of the study are; 1). That there are six village government policies in the development of the Mutiara Bangsa PAUD institution in Petaling village, namely; First, the policy in using curriculum. Second, the policy in providing education funding assistance. Third, policies in the application of cultural education and character education. Fourth, policies in providing assistance to educators to continue their education. Fifth, policies in the formation and authority of school committees, and Sixth, policies in appointing educators. 2). Then there are four types of PAUD Mutiara Bangsa management institutions in Petaling village, namely; First, management in the form of planning. Second, management in the form of organizing. Third, management in the form of implementing learning activities. Fourth, management in the form of supervision. 3). And there are four strategies of government, village and Mutiara Bangsa PAUD institutions in the development of education, children, age, early age, in Petaling village namely; First, the strategy of equal opportunity in obtaining education. Second, the policy relevance strategy. Third, strategies to improve the quality of education and the resources of educators. Fourth, education efficiency strategies.